1987
DOI: 10.1007/bf00584763
|View full text |Cite
|
Sign up to set email alerts
|

Reflex inhibition of efferent renal sympathetic nerve activity by 5-hydroxytryptamine and nicotine is elicited by different epicardial receptors

Abstract: Intrapericardial administration of 5-hydroxytryptamine (5-HT) induced reflex effects consisting in an inhibition of renal sympathetic nerve activity (RSNA), bradycardia and a fall in blood pressure. Nicotine caused the same reflex effects as 5-HT. The reflex effects of both 5-HT and nicotine were abolished by vagotomy. MDL 72222, an antagonist at 5-HT M-receptors, abolished or attenuated the decreases in RSNA, heart rate and blood pressure induced by 5-HT, leaving the reflex effects of nicotine unchanged. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The absence of a depressor response after intrapericardial U-46619 injection suggests that thromboxane A 2 is not an endogenous chemical capable of evoking the coronary chemoreflex. Previous studies demonstrate that intravenous U-46619 evokes a breathing pattern (22,31,32) similar to the vagally mediated pulmonary respiratory chemoreflex (9, 10), and many chemicals, including serotonin, phenyl biguanide, and nicotine, that evoke the pulmonary respiratory chemoreflex also evoke the pulmonary depressor chemoreflex and coronary chemoreflex (10,25,33,35). Thus it seemed reasonable to expect that intravenous and intrapericardial U-46619 would evoke a reflex hypotension.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The absence of a depressor response after intrapericardial U-46619 injection suggests that thromboxane A 2 is not an endogenous chemical capable of evoking the coronary chemoreflex. Previous studies demonstrate that intravenous U-46619 evokes a breathing pattern (22,31,32) similar to the vagally mediated pulmonary respiratory chemoreflex (9, 10), and many chemicals, including serotonin, phenyl biguanide, and nicotine, that evoke the pulmonary respiratory chemoreflex also evoke the pulmonary depressor chemoreflex and coronary chemoreflex (10,25,33,35). Thus it seemed reasonable to expect that intravenous and intrapericardial U-46619 would evoke a reflex hypotension.…”
Section: Discussionmentioning
confidence: 96%
“…The absence of a depressor response after intravenous U-46619 in the present study and in previous studies (4,22) might be due to U-46619's direct vasoconstrictor effect (31,32) overriding the pulmonary depressor chemoreflex. Although a distinction has been made between the coronary chemoreflex [evoked by chemical injection into the coronary arteries (10)] and the epicardial chemoreflex [evoked by chemical injection into the pericardial sac (33)], the same chemicals often evoke both of these reflexes (10,25,33,35). However, in the rabbit for example, intravascular but not intrapericardial phenyl biguanide injection elicits a depressor reflex from the heart (1).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we have previously shown that the actions of CCK on arterial blood pressure and splanchnic sympathetic nerve discharge are dependent on intact vagal afferents (Sartor & Verberne, 2002). Similarly, the sympathoinhibitory effects of PBG are sensitive to vagal section (Mohr et al ., 1987; Evans et al ., 1990). Secondly, CCK 1 receptors and 5‐HT 3 receptors are found on the cell bodies of vagal afferents and are transported to peripheral sites by axonal transport mechanisms (Zarbin et al ., 1981; Kilpatrick et al ., 1990; Lin & Miller, 1992; Corp et al ., 1993; Uneyama et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, 5-HT 3 -receptors seemed only to be present in nerve cells in the heart and might mediate the "von Bezold-Jarisch" reflex [97]. The 5-HT 3 -receptors seem to be found in epicardial afferent sensory nerve ending of the vagus [160]. More recently, however, using a new knockout mouse, 5-HT 3 -receptors were found at least in the ventricle of wild-type mice [110].…”
Section: -Ht-receptors Present In the Heart: Cell And Species Differmentioning
confidence: 99%